PENGARUH CORPORATE SOCIAL RESPONSIBILITY PERCEPTION TERHADAP PERSEPSI PRICE FAIRNESS, PERSONAL SATISFACTION SERTA NIAT BELI, COMPLAINT INTENTION DAN SWITCHING INTENTION - LEN, HE (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This study aims to determine the effect of Corporate Social Responsibility perception toward price fairness perception, personal satisfaction with purchase intention, complaint intention and switching intention. The sample in this study were students Widya Mandala Catholic University Surabaya in Department of Management Retail Concentration. The sampling technique used was purposive sampling. The number of respondents in this study is 120 respondents. Analytical techniques used in this study is Structural Equation Modeling (SEM) using LISREL 8.70 program. The results show that the hypothesis 1 of a Corporate Social Responsibility Perception significant effect on of price fairness perceptions. Hypothesis 2 is Corporate Social Responsibility Perception unsignificant effect on personal satisfaction. Hypothesis 3 that the price fairness perceptions unsignificant effect on of purchase intention. Hypothesis 4 is the perception of price fairness significant effect to the complaint intention. Hypothesis 5 is a perception of price fairness significant effect on switching intention. Hypothesis 6 is a personal satisfaction significant effect to purchase intention. Hypothesis 7 is a personal satisfaction unsignificant effect on complaint intention, hypothesis 8 is a personal satisfaction unsignificant effect on switching intention.